Visions of Saudi Arabia - Farrant, James; Saudi Arabian Oil Company (Saudi Arabia : Saudi Arabian Oil Company, 2007)
Saudi Arabia is a avast and varied land. The center of the Muslim world, site of the world's largest sand desert and home to immense crude oil reserves, it also contains a rich and diverse heritage and an abundance of archeological treasures. The discovery of petroleum catapulted the country into the modern age, and'Visions of Saudi Arabia' visually contrasts exciting new developments against a wealth of cultural traditions and spectacular landscapes in this largely unseen country.
Keywords: Saudi Arabia -- Description and travel